A Convolutional Neural Network-based approach for automatically detecting rainfall-induced shallow landslides in a data-sparse context - Salam, Roquia (2025)
Salam, R., Pla, F., Ahmed, B., & Painho, M. (2025). A Convolutional Neural Network-based approach for automatically detecting rainfall-induced shallow landslides in a data-sparse context. Natural Hazards Research, 5(1), 175-186. https://doi.org/10.1016/j.nhres.2024.09.001 --- This work is the MSc thesis of Roquia Salam and she is grateful to the European Commission for fully funding her Master’s program (Geospatial Technologies) by awarding the Erasmus Mundus Scholarship.